2012
DOI: 10.1007/s00109-011-0841-4
|View full text |Cite
|
Sign up to set email alerts
|

IL-17 producing T cells in mouse models of multiple sclerosis and rheumatoid arthritis

Abstract: Multiple Sclerosis (MS) and Rheumatoid Arthritis (RA) are amongst the most common autoimmune diseases in the northern hemisphere. There is mounting evidence that in both afflictions, not only environmental and genetic factors influence disease, but cellular components such as autoreactive T cells also contribute to pathology. Animal models are key in the study and subsequent therapeutic development for human autoimmune diseases. As patient material is often difficult to obtain and in some cases--as in MS, wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 107 publications
0
19
1
Order By: Relevance
“…It has been shown that IL-17A has antagonistic effect on the IL-12 and IL-10 secreting cells. Moreover, recent studies demonstrated that IL-17A is one of the main cytokines involved in the induction of the EAE,[25] thus, it is difficult to reconcile the reported influence of IL-17A on EAE with our data that showed no changes in the downstream cytokines, IL-12 and IL-10. Further studies need to clarify possible interaction between these cytokines in EAE-induced mice.…”
Section: Discussioncontrasting
confidence: 91%
“…It has been shown that IL-17A has antagonistic effect on the IL-12 and IL-10 secreting cells. Moreover, recent studies demonstrated that IL-17A is one of the main cytokines involved in the induction of the EAE,[25] thus, it is difficult to reconcile the reported influence of IL-17A on EAE with our data that showed no changes in the downstream cytokines, IL-12 and IL-10. Further studies need to clarify possible interaction between these cytokines in EAE-induced mice.…”
Section: Discussioncontrasting
confidence: 91%
“…Although EAE was considered to be a Th1-type disease, the discovery of Th17, IL-17 Tγδ, and IL17-producing innate lymphoid cells (ILC17) and the emerging concept of the plasticity of T cell subsets have led to a more complicated picture for T cell involvement in EAE (Petermann and Korn, 2011; Pollinger, 2012). More recently, the distinction between Th1 and Th17 in EAE and in models of colitis has became less distinct, with the discovery that a new type of Th17 cells, which transiently co-express RORγt and T-bet and therefore are IL-17 + IFNγ + , accumulate in the intestine and CNS, respectively (Ahern et al, 2010; Ghoreschi et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that 7 miRNAs, including miR-16-5p, miR-342-5p, miR-346, miR-518b, miR-760, let-7a-5p and let-7b-5p, were increased, whereas 13 miRNAs, including miR-27a-5p, miR-29a-3p, miR-29b-1-5p, miR-29c-3p, miR-95, miR-149-5p, miR-181c-3p, miR-193a-3p, miR-193-5p, miR-423-5p, miR-532-5p, miR-708-5p and miR-874, were decreased in PBMCs from MS patients after IFN-β therapy 37, which were possibly related with apoptotic processes and IFN feedback loops. In addition, IL-17 was usually up-regulated in MS patients and EAE mice 38. Studies showed that IL-17 suppressed miR-23b expression, which was responsible for the decrease of miR-23b expression in the spinal cords of EAE mice, and in turn, miR-23b down-regulated IL-17 35.…”
Section: Regulation Of Mirnas In Msmentioning
confidence: 99%